An investigation into the effects of project management on a rural poverty alleviation project : the case of the Walda small scale sugar cane farming co-operative - Mhlongo, Mpumelelo Cidrick (My University, 2016)
The management of projects has gained an increasing impetus amongst researchers throughout the world in the last decade. Most of the research projects have focused on which extent can lack of resources affect the implementation of projects in developing countries. Little has been said about the relationship between lack of corporate governance and the management of projects for small scale sugar cane farmers. In this study, the researcher focused on the effects of project management on poverty alleviation and sustainable livelihoods. The study used a mixed method research design which equally employed case study and descriptive approaches. From the quantitative perspective, structured questionnaires were administered, while in the qualitative approach semi-structured interviews were conducted to collect data. Results indicated that the success of projects aimed at poverty alleviation and sustainable livelihoods is dependent on the successful implementation of project management skills. The research amongst others recommend that training and financial support be prioritised for the community projects to achieve their intended objectives.
Thesis (M. Dev.) -- University of Limpopo, 2016.
Keywords: Project management; Rural poverty alleviation projects; Walde Small Scale Farming Project; 658.404; Project management; Poverty